PENGEMBANGAN DATA WAREHOUSE CALL CENTER DENGAN METODOLOGI KIMBALL NINE-STEP PADA BINA SARANA INFORMATIKA - ADJAT SUDRADJAT (Jurnal Informatika, 2015)
ABSTRACT - As an educational institution, Bina Sarana Informatika of course requires summary of information which is comprehensive and sustainable as a support to management in doing evaluation, planning and decision-making in the field of academic services. But the information system from operational data processing today can’t meet the needs, because it’s only able to produce detailed reports periodically. The research studies the development of a data warehouse for Call Center on The Division of Public Information of Bina Sarana Informatika in order to explore the strategic information contained in the operational database and present them in the form of summary information which is useful as input in improving the quality of academic services. By using a nine steps kimball approach, the research produce a data warehouse which is equipped with a web-based presentation application that can be easily accessed by all stakeholders of Bina Sarana Informatika. The development of data warehouse has been able to extract operational data into strategic information summaries that are useful to Bina Sarana Informatika management as supporting in doing evaluation, planning and decision-making in the field of academic services. Keywords : Nine Steps Kimball, Call Center, Data Warehouse, Decision Support. ABSTRAKSI - Sebagai sebuah institusi pendidikan, Bina Sarana Informatika tentu membutuhkan ringkasan informasi yang komprehensif dan berkesinambungan sebagai penunjang bagi manajemen dalam melakukan evaluasi, perencanaan dan pengambilan keputusan di bidang pelayanan akademik. Namun sistem informasi yang berasal dari pengolahan data operasional saat ini tidak dapat memenuhi kebutuhan tersebut, karena hanya mampu menghasilkan laporan–laporan yang bersifat detail dan periodik. Penelitian ini mengkaji pengembangan data warehouse Call Center pada Divisi Informasi Publik Bina Sarana Informatika untuk menggali informasi strategis yang terdapat pada database operasional dan menyajikannya dalam bentuk ringkasan informasi yang berguna sebagai masukan dalam usaha peningkatan kualitas pelayanan akademik. Dengan menggunakan metodologi kimball nine-step, penelitian menghasilkan sebuah data warehouse dilengkapi dengan aplikasi presentasi berbasis web yang dapat diakses dengan mudah oleh seluruh stakeholder Bina Sarana Informatika. Pengembangan data warehouse telah mampu mengekstrak data operasional menjadi ringkasan informasi strategis yang berguna bagi manajemen Bina Sarana Informatika sebagai penunjang dalam melakukan evaluasi, perencanaan dan pengambilan keputusan di bidang pelayanan akademik. Kata Kunci : Nine Steps Kimball, Call Center, Data Warehouse, Decision Support.